EVALUATING THE QUALITY OF VOCATIONAL TOURISM EDUCATION WITHIN THE CONTEXT OF INTERNATIONAL STANDARDS - Yefremtseva, Tatyana; Kireeva, Julia; Tregubenko, Elena; Sorokina, Galina; Solntseva, Oksana (Revista Inclusiones, 2019)
The steady growth of tourism on a global scale in recent years and the changes associated with globalization in all areas of modern life make scientific and professional communities pay special attention to the quality of training for tourism and hospitality. Given the rapid development of communication technologies, increased student mobility and the active cooperation of scientists and professors, the need for an international assessment of the quality of vocational tourism education is especially relevant. The main contradictions between national approaches to quality assessment in different countries and the requirements of international quality standards in the field of tourism education are revealed. The weak connection between educational institutions and employers from the industry deserves special consideration, as a result of which there is a mismatch between the requirements for quality assessment between the university and the industry.